1990
DOI: 10.2307/1940272
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Variation in Tropical Forest Primate Biomass: New Evidence from West Africa

Abstract: To explore sources of variation in tropical forest primate biomass, and, in particular, to test the hypothesis that soil conditions are a major ultimate determinant of the biomass of colobine monkeys and other primates, we compared data on the soils, vegetation, and primate community at a site in West Africa (Tiwai Island, Sierra Leone) with information from other sites, especially two other African sites (Douala—Edea in Cameroon, and Kibale Forest in Uganda). The biomass of eight anthropoid primate species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
217
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(230 citation statements)
references
References 46 publications
11
217
1
1
Order By: Relevance
“…Although Gaboon vipers have been documented to prey on juvenile guenons (Foerster, 2008), to our knowledge no attempt to eat an adult has been observed in the Taï forest. Campbell's monkeys are among the smallest guenons in Taï forest (Oates et al, 1990) and could, therefore, be potential prey. Campbell's monkeys appear to be aware of their dangerousness and respond with ascending in tree and threatening at a safe distance, a behavioural pattern not observed to the mamba model.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gaboon vipers have been documented to prey on juvenile guenons (Foerster, 2008), to our knowledge no attempt to eat an adult has been observed in the Taï forest. Campbell's monkeys are among the smallest guenons in Taï forest (Oates et al, 1990) and could, therefore, be potential prey. Campbell's monkeys appear to be aware of their dangerousness and respond with ascending in tree and threatening at a safe distance, a behavioural pattern not observed to the mamba model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nitrogen is the limiting nutrient in many terrestrial ecosystems and since it is found primarily in protein, herbivores should compensate for this limitation by choosing high protein foods (White 1993). These important ideas proposed by Milton have been applied at the population level by others (McKey et al 1981;Waterman et al 1988;Oates et al 1990;Davies 1994;. For example, Waterman et al (1988) proposed that the weighted contributions of the protein-to-fiber ratios of the mature leaves of the most abundant trees in a particular area could predict the biomass of folivorous colobines.…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…For example, Waterman et al (1988) proposed that the weighted contributions of the protein-to-fiber ratios of the mature leaves of the most abundant trees in a particular area could predict the biomass of folivorous colobines. This index of dietary quality has been applied successfully to predict the biomass of folivorous monkeys at local Ganzhorn 2002) and regional (Waterman et al 1988;Oates et al 1990;Ganzhorn 1995;Chapman et al 2004;Fashing et al 2007) scales. Davies (1994) suggested that the year-round availability of digestible mature leaves with high protein-to-fiber ratios, which are used by colobus species when other, more preferred foods are unavailable, serves to limit the size of colobine populations (i.e., high protein-to-fiber mature leaves are important fallback foods).…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…We thus incorporated data on the nutrient composition of items used by red colobus to examine habitat quality , 2004a. We used the protein : fiber ratio as an index of food quality because it has been found to be a good predictor of folivore leaf choice (Milton 1979) and biomass (Waterman et al 1988, Oates et al 1990, 2004a, Ganzhorn 2002. These relationships have been demonstrated using the overall protein : fiber ratio of mature leaves in an area.…”
Section: Red Colobus Food Availability and Qualitymentioning
confidence: 99%